Absenteeism and the Technical Safety Index of a tertiary hospital nursing team - Trettene, Armando dos Santos [UNESP] (2020)
Objective: To identify the nursing team absenteeism rate, calculate the Technical Safety Index and compare them to the percentage established by the Federal Nursing Council. Method: A descriptive, analytical, and retrospective study which included nursing professionals working in a public and tertiary hospital.The Human Resources Department database of the Institution was used for data collection. Absenteeism was considered as any unplanned absence. Results: Ninety-nine (99) professionals participated, of which 21 were nurses and 78 were nursing technicians. Weekly days off prevailed among the expected absences, with 17% for both categories. Maternity leave prevailed among nurses and medical leave among nursing technicians regarding absenteeism, with averages of 12% and 9%, respectively. The Technical Safety Index was 42% for nurses and 38% for nursing technicians. Conclusion: The nursing team's absenteeism rate was 21.5%, while the Technical Safety Index was 40%, thus constituting higher values than those established by the Federal Nursing Council.